Clinical profile of post coronary artery bypass graft patients undergoing percutaneous coronary intervention in native or graft vessels - Jadhav, Santhosh; Setty, H. S. Natraj; Prakash, Bhanu; C., Yeriswamy M.; Ullegaddi, Arunkumar; Reddy, Babu; Raj, Sathwik; Patil, Rahul; Raghu, T. R.; Manjunath, C. N. (International Journal of Advances in Medicine, 2020)
Background: The PCI target vessel and corresponding outcomes in prior CABG patients are poorly studied. The study aims to determine the predictors and outcomes of native coronary artery and bypass graft percutaneous coronary intervention (PCI) in patients with prior coronary artery bypass graft surgery (CABG). Methods: The factors associated with native and bypass graft PCI were analyzed in prior CABG patients undergoing PCI between July 2011 and December 2013, at Sri Jayadeva Institute Of Cardiovascular Sciences and Research, Bengaluru. Clinical/procedural characteristics and immediate procedural outcomes were recorded and analyzed. Results: During the study period, 76 patients underwent PCI who were before CABG patients. The PCI target was a native coronary artery in 73.6% and a bypass graft in 28.9%. The majority of patients presented more than five years after the CABG (64.4%). Post PCI angina was seen in 7(9.2%), and in 6(7.8%) patients, procedural complications seen. It was found that most PCI was done in patients who presented more than five years after CABG. Conclusions: Most PCIs performed in prior CABG patients are done in native coronary artery lesions.